Agmatine for Pain Management in Dogs With Coxofemoral Joint Osteoarthritis: A Pilot Study - Taguchi, Takashi; Koh, Ronald; Takawira, Catherine; Rademacher, Nathalie; Gilad, Gad M.; Aronson, Randy D.; Lopez, Mandi J. (Frontiers in Veterinary Science, 2018)
Background: Pain from coxofemoral joint (CFJ) osteoarthritis (OA) characteristic of canine hip dysplasia (CHD) afflicts many dogs. Intervertebral disc (IVD) degeneration is a common CFJ OA comorbidity. Pain management with non-steroidal anti-inflammatory drugs (NSAIDs) is standard pain management for degenerative joint disease without or with surgical intervention. Side effects and tolerance with prolonged administration support alternatives to NSAIDs. Agmatine, decarboxylated arginine, reportedly alleviates neuropathic pain, a likely component of OA pain. The objective of this study was to compare treatment response to agmatine and carprofen in dogs with varying degrees of CFJ OA with or without IVD degeneration and to test the hypothesis that agmatine improves hindlimb use comparably to carprofen and more than placebo. Nine hound-type dogs received oral carprofen (4.4mg/kg, sid) for 7 days. Six months later, oral agmatine sulfate (25mg/kg, bid) or placebo (hydroxypropyl methylcellulose, bid) was administered to the same dogs for 28 days with a 2 week washout period between treatments. Validated pain assessment scores were measured before treatment and every seven days throughout the treatment periods. Serum chemistry levels and ground reaction forces (GRFs) were compared among treatments before and after administration. A board-certified radiologist quantified radiographic CFJ OA based on Orthopedic Foundation for Animals criteria and IVD degeneration on magnetic resonance images. Results: There were no detectable adverse side effects or pain score change with any treatment. Significant results included improved GRFs in dogs with mild CFJ OA (N=3) following agmatine administration compared to carprofen or placebo and a trend for improved GRFs in dogs with moderate CFJ OA (N=2) following carprofen versus agmatine or placebo. Neither agmatine nor carprofen improved GRFs in dogs with severe CFJ OA (N=4). The GRFs improved in dogs with IVD degeneration (N=3) following carprofen treatment compared to agmatine or placebo regardless of CFJ OA score but no effect was observed in dogs with normal lumbar spines (N=6). Conclusions: Results support agmatine over carprofen treatment to improve limb use in dogs with early or mild CFJ OA, while carprofen may be the better choice for dogs with moderate CFJ OA or IVD degeneration regardless of CFJ OA severity.